1998
DOI: 10.1093/rheumatology/37.8.895
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for avascular bone necrosis in systemic lupus erythematosus

Abstract: Corticosteroid remains the major predisposing factor for AVN in SLE. Patients who require an initial high-dose steroid for disease control are at risk of AVN, especially if they are positive for the lupus anticoagulant or develop Cushingoid habitus after steroid treatment. High-risk patients should be closely monitored so that early AVN can be diagnosed by sensitive techniques such as magnetic resonance imaging and radioisotope bone scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
3
18

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 10 publications
4
122
3
18
Order By: Relevance
“…Other potential risk factors include vasculitis and Raynaud's phenomenon (12). We and other investigators have previously reported that high-dose prednisone, rather than the total cumulative dose, is an important predictor of AVN (25)(26)(27)(28)(29)(30)(31). While one study has reported that pulse methylprednisolone increases the risk of AVN in SLE, this remains a subject of controversy (27).…”
Section: Discussionmentioning
confidence: 99%
“…Other potential risk factors include vasculitis and Raynaud's phenomenon (12). We and other investigators have previously reported that high-dose prednisone, rather than the total cumulative dose, is an important predictor of AVN (25)(26)(27)(28)(29)(30)(31). While one study has reported that pulse methylprednisolone increases the risk of AVN in SLE, this remains a subject of controversy (27).…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of on April 27, 2019 -Published by www.jrheum.org Downloaded from the use of high-dose CS early in the course of SLE, especially in patients who develop Cushingoid appearance 1,17,32,40,54,65 . However, 1 study of 144 patients followed by periodic MRI (hips and knees) for a minimum of 10 years found no new lesion development in patients receiving a low or medium CS dose (< 30 mg/day of prednisone) 34 .…”
Section: Rheumatologymentioning
confidence: 99%
“…In fact, some authors found that immunosuppressive therapy is a risk factor for ON 17,22,30,32,42,57 . Conversely, these agents could be surrogates for disease activity, which could be a risk for ON.…”
Section: Rheumatologymentioning
confidence: 99%
“…Houssiau et al [24], in their report of a study of ON in SLE patients, stated that the prevalence of ON in SLE did not correlate with aCL; others have found a positive relationship with the presence of lupus anticoagulant [25,26], or between ON and IgG aCL in caucasian patients [23]. In all of these studies, the patients had received GC, which is the major predisposing factor for ON.…”
Section: Mri For Detecting Osteonecrosis In Juvenile Systemic Lupus Ementioning
confidence: 99%